Can high-pressure homogenization cause thermal degradation to nutrients?. (January 2019) - Håkansson, Andreas
Abstract: Although originally developed for fat globule disruption in dairy applications, high-pressure homogenizers are extensively used in other food processing applications. Two newer applications are in forming nanoemulsion for delivering supplemented nutrients and as a preservation technique, both using higher pressures than traditional applications. This has raised concern that friction heat created in the homogenizer causes thermal degradation to temperature sensitive molecules such as nutrients. This contribution uses a numerical model to give insight into temperature profiles for drops in a homogenizer valve and investigates when homogenization at elevated pressures is expected to cause thermal degradation. A fast method for estimating the extent of degradation for a given application is also proposed. It is concluded that no thermal degradation is expected inside the valve, almost regardless of operating conditions, due to the short residence time. Provided that cooling is applied after the homogenizer, degradation downstream of the valve can also be avoided. Highlights: There has been concerns of possible thermal degradation at high pressures in HPHs. A CFD model was used to investigate temperature, trajectories and RTDs. Residence times are short (3–40 ms) and depend only weakly on applied pressure. No degradation is expected, regardless of pressure, due to short residence time. Practical guidelines for estimating temperature and degradation are suggested.